Sebuah Kajian Literatur Tentang Pengalaman Pasien Kanker Dalam Menghadapi Pandemi Covid-19 - Made Satya Nugraha Gautama; Surya Wahyuni; Muflihul Huda; Istiqomah Nur Khasanah; Ulfa Hikmawati; Slamet Aminanto; Stefany Putri Sahureka; Orin Juliastuty Terawati Rizal (NERS Jurnal Keperawatan)
The COVID 19 pandemic has caused various problems for cancer patients. Complaints related to changes in the medication process to the high risk of contracting COVID-19. This qualitative literature study aims to find out what the experiences of cancer patients are like during the COVID-19 pandemic. Articles were searched through Sciencedirect, Sage, Pubmed, and Scopus databases. Keywords using the PCC approach (Population (or participants)/Concept/Context) namely population "patient with cancer OR cancer patient"; concept "experience AND qualitative study" and context "COVID-19 pandemic". The methodological quality of the article findings used assessment tools for Qualitative Research from the Joanna Briggs Institute. A total of 10 articles were analysed. The COVID-19 pandemic provides cancer patients with experiences in decision making and undergoing therapy and has a positive and negative impact on cancer patients and caregivers. During the pandemic, cancer patients have many considerations related to information, family involvement, and treatment decisions during the pandemic. The anxiety experienced is a special challenge felt by cancer patients and caregivers during a pandemic. It is hoped that care services are aware of this situation, reduce the worries of cancer patients and treatment can still run well during a pandemic.